1998
DOI: 10.1128/jcm.36.8.2205-2209.1998
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Meningococcal Meningitis by Broad-Range Bacterial PCR with Cerebrospinal Fluid

Abstract: We used broad-range bacterial PCR combined with DNA sequencing to examine prospectively cerebrospinal fluid (CSF) samples from patients with suspected meningitis. Fifty-six CSF samples from 46 patients were studied during the year 1995. Genes coding for bacterial 16S and/or 23S rRNA genes could be amplified from the CSF samples from five patients with a clinical picture consistent with acute bacterial meningitis. For these patients, the sequenced PCR product shared 98.3 to 100% homology with the Neisseria meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 19 publications
3
36
0
2
Order By: Relevance
“…It has been reported that PCR amplification of numerous targets, such as the 16S rRNA gene, the 16S-23S rRNA interspacer region, the IS1106 region and the PorA gene, have been used to detect organisms in CSF and blood specimens from patients with meningitis (Radström et al, 1994;Hall et al 1995;Kotilainen et al 1998;Glustein et al 1999;Rantakokko-Jalava et al 2000;Seward and Towner, 2000). Molecular-based diagnostic approaches are now more frequently used alongside conventional microbiological techniques in the diagnostic clinical microbiology laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PCR amplification of numerous targets, such as the 16S rRNA gene, the 16S-23S rRNA interspacer region, the IS1106 region and the PorA gene, have been used to detect organisms in CSF and blood specimens from patients with meningitis (Radström et al, 1994;Hall et al 1995;Kotilainen et al 1998;Glustein et al 1999;Rantakokko-Jalava et al 2000;Seward and Towner, 2000). Molecular-based diagnostic approaches are now more frequently used alongside conventional microbiological techniques in the diagnostic clinical microbiology laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bacterial DNA was detected in SF of 33% of ReA patients (Figure 4), and was consistent with the previous observations (39, 40). The PCR primers used have also been tested in previous studies and shown to cover most bacteria (26, 36, 37). It should be noted that the pan‐bacterial PCR is extremely sensitive to contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The primers for 23S and 16S rDNA PCR have been described before. Both primer pairs, MS‐37 and MS‐38 for the 23S PCR and fD1 and rP2 for 16S PCR, have been used for diagnosis of bacterial infection for a variety of clinical samples (26, 36, 37).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of N. meningitidis DNA may be performed by amplification of conserved genes such as the genes encoding 16S rRNA. This amplification may target specific or universal sequences within these genes, and further sequencing the PCR product allows the identification of N. meningitidis (Kotilainen et al, 1998;Bäckman et al, 1999;Corless et al, 2000;Mölling et al, 2002).…”
Section: Validation Of Protocolsmentioning
confidence: 99%